2020
DOI: 10.1002/jcp.29748
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 increases adrenal androgen release by regulating the expression of steroidogenic proteins in NCI‐H295R cells

Abstract: The purpose of this study was to investigate the potential mechanism of interleukin‐6 (IL‐6) on the stimulation of excessive androgen secretion in human NCI‐H295R adrenocortical cells. We performed transcriptome sequencing of cancer and paracancerous tissues obtained from functional adrenal cortical adenomas. The secretion of dehydroepiandrosterone sulfate (DHEAS) in NCI‐H295R cells was detected by a chemiluminescence assay. The expression of messenger RNA (mRNA) was detected by real‐time polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…Providing evidence of a role for altered cytokine levels in the observed normalisation of corticosterone fluctuations in SGLT2 null mice, treatment of adrenal gland cells with IL-6 upregulated CYP11A1 and HSD3B2, in line with previous findings (39). An upward trend was also observed following treatment with leptin (40) and IL-1β (41), while IL-10 and TGFβ1 had no effect, again mirroring earlier results (42,43).…”
Section: Discussionsupporting
confidence: 87%
“…Providing evidence of a role for altered cytokine levels in the observed normalisation of corticosterone fluctuations in SGLT2 null mice, treatment of adrenal gland cells with IL-6 upregulated CYP11A1 and HSD3B2, in line with previous findings (39). An upward trend was also observed following treatment with leptin (40) and IL-1β (41), while IL-10 and TGFβ1 had no effect, again mirroring earlier results (42,43).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, LH and DHEAS hormone levels were significantly correlated with IL-6 levels. Interestingly DHEAS and IL-6 have a correlation in healthy women but not in PCOS women (24). Additionally, ANOVA and following Bonferroni multiple comparisons showed that DHEAS level had significant changes between groups and among subjects in PCOS women and control women.…”
Section: Discussionmentioning
confidence: 85%
“…Nagy intenzitású és hosszú időtartamú edzés hatására a limfociták száma csökken, míg a neutrofilek koncentrációja nő, például az adrenalin és CTOL hatására [101]. De a glükokortikoid vonalon túl elősegítheti az androgének szekrécióját az olyan gének expressziójának szabályozásával, amelyek az androgének szintetikus útvonalához kötöttek [102]. Az IL-6 mellett a szintén citokinek közé tartozó tumor nekrózis faktor-alfa (TNF-α) is jelen van az emberi mellékvesekéregben is.…”
unclassified